Ayurveda Perspective on Visarpa Vyadhi and its Management (International Journal of Ayurveda and Pharma Research, 2023)
Skin is the largest organ of the body which acts as a first line of defense in providing resistance to the body. The aggravation of various Dhatus and Doshas result in skin diseases. More than one-fifty skin related diseases are mentioned in various Ayurvedic texts. They are categorized as Visarpa, Kustha, Shotha, Upadansh etc. Visarpa is a very common disease mentioned in Ayurvedic texts which spreads in body in various directions. It is said to be caused by Varicella zoster virus as per modern concept. It manifests as Daha, Jwara, Anunnatashopha and Vedana. Around 20-30% sufferers of various skin ailments are demonstrated through large community prevalence study. A 40-year-male presented along with the vesicular lesions on his neck region associated with mild fever, itching, and pain on the local lesion. He was administered with 250mg of Kamadudha rasa (plain) twice a day before meals with milk, Chandrakala rasa 250mg twice a day, Paripathadi kwatha 2 tsp twice a day and Shatadhauta ghrita for local application on the lesions. The patient reported on the 5th day with significant relief in the size and shape of the facial lesions and other symptoms. The scars limited to minimal without any inflammatory signs by the 7th day of follow-up. Above medications are two readily available and cost-effective compound Ayurvedic formulations, which can be used in the management of herpes zoster infection, especially in low-resource settings.